2018
DOI: 10.1080/01635581.2018.1446088
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D Supplementation on Breast Density Changes: A Clinical Trial Study

Abstract: This study showed that monthly consumption of 50,000 IU of vitamin D supplementation for 1 yr did not affect breast density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Low levels of serum Vitamin D have been assumed as a risk factor for endometriosis and for increased MBD. However, this relation has been highly demonstrated for the former [ 29 ], but not in the latter condition [ 30 ]. Also, use of dairy products might lower the risk of endometriosis [ 31 ], while the few studies about the association of these products with MBD have showed controversial results from no relation to a negative association [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of serum Vitamin D have been assumed as a risk factor for endometriosis and for increased MBD. However, this relation has been highly demonstrated for the former [ 29 ], but not in the latter condition [ 30 ]. Also, use of dairy products might lower the risk of endometriosis [ 31 ], while the few studies about the association of these products with MBD have showed controversial results from no relation to a negative association [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the present study, we found a marginally significant increasing breast density with vitamin D intake (p-value = 0.047). The association between vitamin D and MBD remains poorly understood in many studies [43][44][45] due to differences in study designs, MBD assessment, vitamin D exposure assessment methods, categorization of women with some variables such as menopause, lack of attention to seasonal variation, diet, and other considerations. Since the vitamin D intake in this study was based on the self-reported of women and finding an association between vitamin D intake and breast density was not our goal, this result may be crude and inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evaluated the effects of aspirin and metformin on MBD with inconsistent results (33)(34)(35)(36). In addition some researches have shown that higher vitamin D and calcium intake are associated with decreased MBD (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%